The formation of tonalitic and granodioritic melt from Venusian basalt - Wang, Yao Jui; Shellnutt, J. Gregory; Kung, Jennifer; Iizuka, Yoshiyuki; Lai, Yu-Ming (Scientific reports, 2022)
The crust of Venus is composed of the low lying volcanic planitiae and the elevated, deformed tesserae. It is thought that the tesserae may be composed of silicic igneous rocks and that it may resemble proto-continental crust. The initial development of terrestrial continental crust is likely due to melting and deformation of primitive mafic crust via mantle-plume upwelling and collisional plate processes. Unlike Earth, the lithosphere of Venus is not divided into plates and therefore evolved continental crust, if present, developed primarily by melting of pre-existing mafic crust. Here, we report the results of high pressure equilibrium partial melting experiments using a parental composition similar to the basalt measured at the Venera 14 landing site in order to determine if silicic melts can be generated. It was found that at pressures of 1.5 GPa and 2.0 GPa and temperatures of 1080 °C, 1090 °C, and 1285 °C that tonalitic and granodioritic melts can be generated. The experimental results indicate that silicic rocks may be able to form in the crust of Venus providing the thermal regime is suitable and that the lower crust is basaltic. The implication is that the older, thicker regions of Venusian crust may be partially composed of silicic igneous rocks.